2009
DOI: 10.1007/s12185-009-0428-9
|View full text |Cite
|
Sign up to set email alerts
|

Mikulicz’s disease with severe thrombocytopenia following autologous stem cell transplantation in a multiple myeloma patient

Abstract: We report the first case of Mikulicz's disease (MD) occurring 2 years after autologous peripheral blood stem cell transplantation (PBSCT) for multiple myeloma (MM). A 70-year-old man developed bilateral enlargement of parotid and submandibular glands. The patient had previously received 2 courses of autologous PBSCT for IgG-kappa type MM, and had been stable for 2 years. This salivary gland enlargement was initially felt to represent a recurrence of MM, since along with gland swelling, IgG was also elevated. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…10,16 In addition, impaired immunity due to autologous transplantation might also account for autoimmune thrombocytopenia. 3 In summary, this novel study described a rare case of IgG4-related MD complicated with autoimmune thrombocytopenia without any hematologic malignancies. Although IgG4-related MD had a favorable response to steroid therapy, the steroid dose was recommended to be high and immunosuppressive agents helped in reducing the dose of steroids for the patient suffering from IgG4-related MD with thrombocytopenia.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…10,16 In addition, impaired immunity due to autologous transplantation might also account for autoimmune thrombocytopenia. 3 In summary, this novel study described a rare case of IgG4-related MD complicated with autoimmune thrombocytopenia without any hematologic malignancies. Although IgG4-related MD had a favorable response to steroid therapy, the steroid dose was recommended to be high and immunosuppressive agents helped in reducing the dose of steroids for the patient suffering from IgG4-related MD with thrombocytopenia.…”
Section: Discussionmentioning
confidence: 76%
“…In that case, the patient developed severe thrombocytopenia after autologous PBSCT for MM. 3 This study reported the first case of IgG4-related MD with immune thrombocytopenia without hematologic malignancies. In the present case, the diagnosis of IgG4-related MD was confirmed by the pathological examination of submandibular glands.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation